Water Stress Adaptations by Rhododendron arboreum Smith in The Himalayan Treeline Environment: Rhododendron arboreum: Water Stress Adaptations at the Himalayan Treeline - Singh, Nandan; Tewari, Ashish; Shah, Shruti; Mittal, Amit (Vietnam Journal of Science and Technology, 2024)
Drought is amongst the most important climatic events which can severely impact natural ecosystems. The under-canopy Indian Himalayan tree species are less studied on water stress in harsh climatic conditions. Rhododendron arboreum is an ecologically and economically important tree species and distributed between 1500–3500 m asl in the Himalayan ecosystems. In this study, we have tried to assess the water stress adaptations by R. arboreum near the treeline ecotone located at 30°11´02˝N and 79°39´36˝E between 3100 and 3500 m asl elevation. Water potential (Ψ) was measured using a Pressure chamber and leaf conductance with the help of AP4 porometer. Soil moisture (Sm) across the depths was highly variable (p<0.05). The pre-dawn water potential (ΨPD) of R. arboreum tree varied between -0.12 and -0.91 MPa. ANOVA showed that the ΨPD of R. arboreum seedlings varied significantly across the years, seasons, and sites (p<0.05). The decline in osmotic potential at full turgor (Ψπ100) was -1.18 to -1.20 MPa in trees and -1.42 to -1.72 MPa in seedlings. The morning leaf conductance (gwAM) of R. arboreum trees ranged from 58.00 to 271.68 m mol m-2 sec-1. Correlation showed that the maximum leaf conductance in R. arboreum trees was observed when the ΨPD was -0.5 to -0.9 MPa. Water uptake function in plants is generally affected by winter frost which can change the Ψ, osmotic potential, and leaf conductance of plants. The ΨPD in the species was relatively high across all seasons in the treeline areas to disrupt physiological activities.